Review: The parables of Jesus the Galilean: Stories of a social prophet - Martin Laubscher (Acta Theologica)
From text: It has become fashionable in recent scholarship to claim that it is methodologically impossible and hermeneutically undesirable to uncover the meaning of the parables of Jesus outside their literary contexts in the New Testament. Some scholars even go as far as to claim that the interpretation and application of the parables in the Synoptic Gospels are representative of the intent of the historical Jesus.